A well-defined thermo- and pH-responsive double hydrophilic graft copolymer bearing pyridine-containing backbone. Issue 19 (26th April 2022) - Chen, Rang; Jiang, Xue; Lu, Guolin; Liu, Wenbin; Jin, Weize; Tian, Guojian; Huang, Xiaoyu
Abstract : We report a thermo- and pH-responsive double hydrophilic graft copolymer possessing pyridine-containing backbone. Abstract : Graft copolymers have extensive applications in material science because of the tunable nature of their backbones and side chains and the diverse morphologies of their aggregates. Recent studies have mainly focused on amphiphilic graft copolymers containing hydrophobic backbones and hydrophilic side chains. To the best of our knowledge, no studies have reported amphiphilic graft copolymers bearing pyridine-containing hydrophilic backbones. Based on the design of functional monomers, a new trifunctional acrylate monomer, PyMCIBMA, was prepared in two steps via a Morita–Baylis–Hillman reaction, followed by reaction with 2-chloroisobutyryl chloride. Reversible addition–fragmentation chain transfer (RAFT) polymerization of PyMCIBMA monomer was performed to generate a well-defined poly(PyMCIBMA) homopolymer possessing a Cl-containing ATRP initiating group in each repeat unit. Next, a series of well-defined double hydrophilic graft copolymers bearing densely distributed poly( N -isopropyl acrylamide) (PNIPAM) side chains along the backbone on every unit, PPyMA- g -PNIPAM, was synthesized via atom transfer radical polymerization (ATRP) initiated by poly(PyMCIBMA) homopolymer. The resulting graft copolymers exhibited intriguing dual temperature- and pH-sensitive behavior, signifying their potential applications in controlled delivery as polymer–drug nanocarrier.